The Influence of Organizational Culture and Leadership on Lecturer Performance - Hesty Amalia Gultom; Paningkat Siburian; Nagian Toni (Proceeding of The International Conference on Business and Economics, 2023)
This research aims to analyze the influence of organizational culture and leadership on the performance of private university lecturers in Sibolga City and Central Tapanuli Regency, North Sumatra. This research uses a quantitative approach, with a quantitative method in the form of a survey. The researcher determined that the sample in the research was private university lecturers in Sibolga City and Central Tapanuli, North Sumatra Province, with a total of 172 people. The researcher took the entire population to be used as a sample of 120 people. . Data collection uses questionnaires, and data analysis uses multiple regression analysis. The research results show that organizational culture and leadership significantly affect the performance of lecturers at private universities in Sibolga City and Central Tapanuli Regency, North Sumatra.